Idiopathic herniation of the thoracic spinal cord: an often mis-diagnosed clinical entity - Runza, Giuseppe; Maffei, Erica; Cademartiri, Filippo (Acta Biomedica Atenei Parmensis, 2021)
Since 1974, when Wortzman et al were the first to describe a case of idiopathic spinal cord herniation (ISCH), the number of reported cases has increased owing to magnetic resonance imaging (MRI) now is routinely available for patients with myelopathy and spinal surgeons are becoming more familiar with this clinical entity. This extremely rare herniation occurs exclusively in the thoracic spine, causing slowly progressive myelopathy. Diagnosis is based on ventral displacement of the spinal cord in the thoracic spine. MRI is the technique of choice to exclude a posterior arachnoid cyst, the most common mistaken diagnosis, and to recognize a spinal cord herniation when an anterior dural defect is present. A case of ISCH is reported and a Literature review of this clinical entity often mis-diagnosed has been obtained.